Modern Indonesian theater in the 1980s: A criticism of the aesthetic hegemony of the new order - Novianto, Wahyu; Guntur , Guntur; Faruk , Faruk; Simatupang , G.R. Lono L. (Gelar: Jurnal Seni Budaya, 2024)
This article discusses the practices and discourse of modern Indonesian theater in the 1980s as a form of resistance to the aesthetic hegemony of the New Order. For 32 years, under the government of Soeharto, freedom of expression was increasingly suppressed, including in the art of theater. Various forms of resistance emerged from theater groups, through practices and discourse that wished to seize the dominance of the New Order’s aesthetic ideology. This research aims to reveal how modern Indonesian theater functioned as a tool of counter-hegemony through the practices and discourse it developed. The research approach uses a critical paradigm with a qualitative method. The primary data are documentation of theater performances from the 1980s and the secondary data are taken from literature about the New Order and mass media articles. A dialogical analysis was carried out to discuss the various data and to explore the relationship between art and efforts to build a counter-hegemony. The research results show that modern Indonesian theater used artistic strategies such as symbolism, humor, and exploration of local traditions to convey criticism, and developed an alternative discourse that challenged the domination of noble (adiluhung) aesthetics. The study concludes that the practices and discourse of modern Indonesian theater in the 1980s reflected a process of negotiation between tradition and modernity, aesthetics and politics, and became a space for symbolic resistance to the New Order system. Through fluid, innovative art forms, theater functioned as a medium of social awareness and a tool of change amidst the constraints of the authoritarian regime.